THE APPLICATION OF Fe AND Cr(III) IN GROWING MEDIA AND ITS EFFECT ON PLANT GROWTH AND Cr(III) OXIDATION ON Tagetes erecta - Penina Intansari; Sri Kasmiyati; . Sucahyo (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
The oxidation of Cr(III) to Cr(VI) in the environment has a detrimental impact because it can change the form of non-toxic Cr(III) to Cr(VI), which is toxic to organisms. The study aimed to examine the effect of the application of iron (Fe) and trivalent chromium (Cr(III)) compounds in Tagetes erecta growing media on growth and Cr(III) oxidation. Concentrations of Cr(III) 0, 100, and 500 mg/L and Fe 0, 3, 15, and 30 mg/L were applied to the growing media of T. erecta as the model plant. The growth and accumulation of Cr(VI) in plants were measured to determine the effect of Fe and Cr(III) treatment on growth and Cr(III) oxidation. The accumulation of Cr(VI) in the roots and shoots of T. erecta increased significantly due to the addition of Fe in the growing media treated with Cr(III). The highest accumulation of Cr(VI) in the roots and shoots of T. erecta found in the treatment of Cr(III) 500 mg/L and Fe 30 mg/L, were respectively 0.092 g/L and 0.070 g/L. The addition of Fe in growing media containing Cr(III) increased plant height, root length, and shoot dry weight but decreased leaf number and root dry weight. T. erecta root biomass was more affected by the toxic impact of Fe than Cr(III). On the other hand, the inhibition of leaf formation was caused by the toxic effect of Cr(III) rather than Fe. Oksidasi Cr(III) menjadi Cr(VI) di lingkungan mempunyai dampak merugikan, karena dapat mengubah bentuk Cr(III) dari tidak toksik menjadi bentuk Cr(VI) yang toksik bagi organisme. Tujuan penelitian adalah untuk mengkaji efek aplikasi senyawa besi (Fe) dan kromium trivalen (Cr(III)) dalam media tanam Tagetes erecta terhadap pertumbuhan dan oksidasi Cr(III). Konsentrasi Cr(III) 0, 100 dan 500 mg/L dan Fe 0, 3, 15 dan 30 mg/L diaplikasikan dalam media tanam T. erecta sebagai tanaman uji. Pertumbuhan dan akumulasi Cr(VI) pada tanaman diukur untuk mengetahui efek perlakuan dan mendeteksi terjadinya oksidasi Cr(III). Akumulasi Cr(VI) pada akar dan pucuk T. erecta mengalami peningkatan secara nyata akibat penambahan Fe dalam media tanam yang diberi perlakuan Cr(III). Akumulasi Cr(VI) pada akar dan pucuk T. erecta tertinggi dijumpai pada perlakuan Cr(III) 500 mg/L dan Fe 30 mg/L berturut-turut adalah 0,092 g/L dan 0,070 g/L. Penambahan Fe dalam media tanam mengandung Cr(III) meningkatkan pertumbuhan tinggi tanaman, panjang akar dan berat kering pucuk, namun menurunkan jumlah daun dan berat kering akar. Biomassa akar T. erecta lebih dipengaruhi oleh efek toksik Fe dibandingkan Cr(III), sebaliknya penghambatan pembentukan daun lebih disebabkan oleh efek toksik Cr(III) daripada Fe.